Evaluation of circulating tumor DNA as a biomarker in childhood Hodgkin lymphoma using liquid biopsy-informed sequencing panels - Lundqvist, Caroline (My University, 2026)
Hodgkin lymphoma (HL) is the most common lymphoma in children and adolescents. Although treatment outcomes are generally favorable, long-term treatment-related side effects are common among HL survivors. Current monitoring methods include positron emission tomography/computed tomography (PET/CT), which has limited sensitivity and may lead to unnecessary treatment escalation. More sensitive monitoring approaches could therefore improve treatment decisions while reducing exposure to treatment-related toxicity. Circulating tumor DNA(ctDNA)analysisusing liquid biopsies has emerged as a promising approach for disease monitoring. This study aimed to evaluate whether liquid biopsy-informed sequencing panels could be designed for longitudinal ctDNA monitoring in children with HL. Patient-specific single nucleotide variants (SNVs) were identified through whole-exome sequencing (WES) of plasma cell-free DNA (cfDNA). Personalized sequencing panels were designed based on the selected SNVs, and sequencing libraries were constructed and evaluated using SiMSen-Seq. Longitudinal plasma samples were subsequently analyzed to evaluate ctDNA levels in relation to treatment outcomes. Personalized sequencing panels targeting patient-specific mutations were successfully designed for patients with stage IV HL. CtDNA levels correlated with treatment outcomes, suggesting that longitudinal ctDNA analysis may serve as a complementary tool for treatment monitoring. Additionally, the study demonstrated the importance of applying stricter variant filtering and manual review of variant reads in Integrative Genomics Viewer (IGV) for reliable SNV selection. Variant allele frequencies were generally higher in diagnostic plasma cfDNA compared to tumor tissue DNA, supporting the use of liquid biopsy as a suitable starting material for mutation detection in pediatric HL. Several technical and clinical limitations were identified. Most SNVs detected in patients with stage II–III disease were likely sequencing artifacts, suggesting that the sensitivity of 100× WES is insufficient for patients with lower tumor burden. As a result, clinical evaluation was restricted to stage IV patients. In addition, the small cohort size and limited clinical variability restricted the assessment of the clinical utility of the method. In conclusion, liquid biopsy-informed ctDNA monitoring shows potential as a complementary approach for treatment monitoring in pediatric HL. Further studies with deeper sequencing approaches and larger patient cohorts are needed to evaluate the broader clinical applicability of the method.
Keywords: Liquid biopsy; Biomarker; Circulating tumor DNA; Childhood Hodgkin lymphoma; SiMSen-Seq.